Walking in ever-changing paths a recording of Krus na Ligas through frottage and video documentation - Dominguez, Brisa Amir C.; Abaño, Ma. Victoria; Romero, Riza (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
The thesis examines how walking can record, through frottage and video documentation, a community's changing landscape and its effect on emotions and behaviors of inhabitants. It aims to realize the connections between the place and emotion; and to use the body as a secondary tool to gather data, the result of which are presented in an installation that features frottage and video documentation. The site of this thesis is Krus na Ligas where I was born. It is a community located within the vicinity of the University of the Philippines in Diliman, which has existed for almost four centuries. The changing landscape is recorded by using the frottage technique and montage video documentation. The frottage technique uses continuous rolls of thermal papers and graphite to depict the concept of impermanence. The montage video documentation highlights the walking experience and captures the sounds and visuals of the changing landscapes. These outputs are presented in an installation art that stimulates the experience of walking and audio-visual recording of the ever-changing paths of Krus na Ligas. The thesis concludes that walking is important to the visual artists. In addition, it demonstrates the value of combining frottage and video as artistic mediums to capture the changing landscape of a community and effects on the emotions and behaviors of the inhabitants.
Thesis (Bachelor in Fine Arts (Painting))--University of the Philippines Diliman
Bibliography : leaves 19-20.
Keywords: Rubbing